PENGARUH SIMPAN PINJAM PEREMPUAN (SPP) PROGRAM PNPM MANDIRI PERDESAAN TERHADAP PENGEMBANGAN USAHA MASYARAKAT DESA PLEMAHAN, KECAMATAN SUMOBITO, KABUPATEN JOMBANG - Romadlona, Wulandari; Dinaloni, Diah (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This research aims to determine the the influence of the PNPM Mandiri Rural Women's Savings and Loans Program (SPP) on business development in the community of Pringan Village, Sumobito District, Jombang Regency. This research used a quantitative approach with a research population of 195 people. The sample size calculation was determined using the Slovin formula. Based on this formula, the number of samples taken in this research was 66 people. Meanwhile, the sampling technique used by researchers is proportional random sampling technique. Data collection was carried out by means of observation, interviews, documentation and distributing questionnaires with a Likert scale. Each variable is measured using validity and reliability tests. Data analysis used the normality test, t test, simple linear regression test, and coefficient of determination test. The research results obtained a significance value of 0.020, smaller than 0.05 and a calculated t value of 2.394, greater than the t table value of 1.99834, so it can be concluded that there is an influence of the Women's Savings and Loans (SPP) Program of the PNPM Mandiri Rural Program on business development